IMPLEMENTATION OF THE FORMING PROGRAM FOR FAMILY PLANNING IN THE BABAKAN VILLAGE PANGANDARAN DISTRICT: Array - Indri Rahma Yusmayanti; Agus Nurulsyam Suparman (JGSRD: Journal of Government Science and Rural Development, 2020)
This study aims to determine the implementation of the Family Planning Village in Babakan Village, Pangandaran District, Pangandaran Regency. The research method used in this research is descriptive qualitative research methods, data collection techniques through interviews and literature study. Data analysis was carried out through triangulation techniques in which the collected data was reduced, translated and analyzed in descriptive form. The results of research conducted in the Implementation of the Family Planning Village Formation Program have not been carried out optimally, it is seen from several dimensions that are still less than optimal, namely: employee understanding of the KB village; Human resource factors are felt to be lacking; and the availability of funds and equipment, in the dimension of limited sources of funds and equipment to support programs implemented by employees in the field. However, with minimum resources try as much as possible by using a variety of available resources to the maximum. Thus it can be seen how the Implementation of the Establishment of the Family Planning Village in Babakan Village has been carried out to the maximum extent possible with various limitations.